(untitled) - Cornforth, Derek H. (Hoboken, N.J., 2005)
The authoritative guide to landslide investigation, evaluation, and mitigation design. To-the-point summaries explain presented techniques without confusing jargon, and dozens of succinct case histories integrated throughout the book serve as useful examples. In addition, twelve expanded case histories illustrate in depth many aspects of the landslide events and remediation strategies covered.
Keywords: Soil mechanics,Landslide hazard analysis,Landslides